Nomogram for Estimating Overall Survival in Patients With Metastatic Pancreatic Cancer - Goldstein, David (Pancreas, 2020)
OBJECTIVES: This analysis investigated nomogram use to evaluate metastatic pancreatic cancer prognosis. METHODS: Thirty-four baseline factors were examined in the Metastatic Pancreatic Adenocarcinoma Clinical Trial (MPACT) (nab-paclitaxel plus gemcitabine vs gemcitabine) data set. Factors significantly (P < 0.1) associated with overall survival (OS) in a univariable model or with known clinical relevance were tested further. In a multivariable model, factors associated with OS (P < 0.1) were selected to generate the primary nomogram, which was internally validated using bootstrapping, a concordance index, and calibration plots. RESULTS: Using data from 861 patients, 6 factors were retained (multivariable analysis): neutrophil-lymphocyte ratio, albumin level, Karnofsky performance status, sum of longest diameter of target lesions, presence of liver metastases, and previous Whipple procedure. The nomogram distinguished low-, medium-, and high-risk groups (concordance index, 0.67; 95% confidence interval, 0.65–0.69; median OS, 11.7, 8.0, and 3.3 months, respectively). CONCLUSIONS: This nomogram may guide estimates of the range of OS outcomes and contribute to patient stratification in future prospective metastatic pancreatic cancer trials; however, external validation is required to improve estimate reliability and applicability to a general patient population. Caution should be exercised in interpreting these results for treatment decisions: patient characteristics could differ from those included in the nomogram development.